The ups and downs of maritime spatial planning in Portugal - Calado, H. (2024)
Funding Information: This work was supported by project OceanPlan (Marine Spatial Planning Under a Changing Climate) funded by the Portuguese Foundation for Science and Technology (FCT) under grant agreement no. PTDC/CTA-AMB/30226/2017 . Publisher Copyright: © 2023 The Authors